2018
DOI: 10.1186/s12886-018-0829-8
|View full text |Cite
|
Sign up to set email alerts
|

The increasing prevalence of myopia and high myopia among high school students in Fenghua city, eastern China: a 15-year population-based survey

Abstract: BackgroundMyopia is the leading cause of preventable blindness in children and young adults. Multiple epidemiological studies have confirmed a high prevalence of myopia in Asian countries. However, fewer longitudinal studies have been performed to evaluate the secular changes in the prevalence of myopia, especially high myopia in China. In the present study, we investigated trends in the prevalence of myopia among high school students in Fenghua city, eastern China, from 2001 to 2015.MethodsThis was a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
137
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(155 citation statements)
references
References 35 publications
9
137
5
4
Order By: Relevance
“…The Waterloo Eye Study showed a long-term increase in myopia prevalence also in the United States [36]. The prevalence rate reached 42.4% in 10 to 15-year-old children, and 53.9% in 15 to 20-year-old; this was significantly higher than the 21% peak value (in those aged 20-30 years) reported in a comparable study done in 1892 [43].…”
Section: Change Over Timementioning
confidence: 71%
See 1 more Smart Citation
“…The Waterloo Eye Study showed a long-term increase in myopia prevalence also in the United States [36]. The prevalence rate reached 42.4% in 10 to 15-year-old children, and 53.9% in 15 to 20-year-old; this was significantly higher than the 21% peak value (in those aged 20-30 years) reported in a comparable study done in 1892 [43].…”
Section: Change Over Timementioning
confidence: 71%
“…In a study from the Haidian District in Beijing, China, the prevalence of myopia in a cohort of 15-year-old schoolchildren increased from 55.95% in 2005 to 65.48% in 2015 [10]. In Fenghua city, eastern China, the prevalence of myopia in high school students increased from 79.5% in 2001 to presented as a population-based cross-sectional survey, however, the results report that the prevalence rate among initial emmetropes and hyperopes, after 5 years 87.7% in 2015, and high myopia (SER greater than − 6.0 D) was a major contributor to this increase [43]. In Western China not only myopia prevalence increased, but also a higher rate of annual myopia progression was recently noted [13].…”
Section: Change Over Timementioning
confidence: 86%
“…During the same time period, prevalence in the UK among approximately 11-year-old children increased from 4.0 [2] to 11.9% [3]. The situation is even more alerting in East Asia, with a prevalence of nearly 88% in 2015 in some parts of eastern China [4]. Myopia can be corrected by spectacle wear or surgery, but higher myopia (-6D or more) is associated with an increased risk of cataract, glaucoma, and myopic macular degeneration [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of myopia has dramatically risen over the past 60 years with significant regional variations in myopia prevalence across the world, from approximately 15 per cent of adults in Australia, to 70–90 per cent in South East Asian countries such as China, South Korea, Singapore, and Taiwan . By 2050, it is estimated that 50 per cent of the global population will be myopic (> −0.50 D), with one‐fifth of these being highly myopic (> −5.00 D) .…”
mentioning
confidence: 99%